Salinization and soil degradation: an indication of the adoptionwith inadequate use of technology/1707Salinizaçãoe degradação de solo:umaconsequência daadoçãoeuso inadequado detecnologia - Danila Rodrigues Brito; Cleiciane Marques Silva; Victoria Eica de Carvalho Berbary; Claudia Cseko Nolasco de Carvalho; Fabio Carvalho Nunes; Cibele Merched Gallo (Universidade Estadual de Alagoas, 2020)
The semiarid region of Alagoas has its economy based on agricultural production. The animal husbandry is predominantly extensive, however, due to scarce and uneven rainfall, it is common to plant forage species for silage, haymaking and farm supply. Despite the high production potential, the edaphoclimatic conditions and the absence of soil maintenance practices or use of incorrect practices of soil maintenance and conservation, factors that condition the good result, can lead to a production decline and soil and pasture degradation. Chemical, physical and biological alterations of the soil are indicative of the environmental quality. The evaluation of these attributes, associated with visual field indicators(vegetation, erosion) provide evidence of soil fertility and pasture sustainability. Agrasslandcultivated with irrigated foragemaize was evaluated in the county of Santana do Ipanema/AL, Brazil. Data on vegetation cover, soil and water used for irrigation were correlated. The degradation state of the grassland was evaluated through the method of Spain & Gualdrón (1991).The water with inappropriate characteristics for irrigation usage associated to the supply usage and improperly implemented soil and pastures practicescompromises the sustainability of forage production in the area. The harmful effects caused by excess salts can be seen in the results of the soil analysis, which presents pH 13.8, PST 6.9 and 100% base saturation. The total vegetal cover found in the area was 35%and the result in the green maizeproduction was negative.These values account for the very high degradation degree of the grassland.